Demographical analyses of lung cancer incidence and mortality trends in Vojvodina - Petrović Vladimir (Archive of Oncology, 2005)
BACKGROUND: Studies conducted in Vojvodina from 1960 to 1978 showed that the highest number and percentage of lung cancer cases and deaths occurred in seventh decade of life. Our aim was to analyze epidemiological characteristics of lung cancer in Vojvodina demographically from 1989 to 1998. METHODS: Data used for analyses were provided by the Cancer Registry of Vojvodina from the Institute of Oncology Sremska Kamenica. Descriptive epidemiological method was used. RESULTS: The sex ratio (males to females) of lung cancer incidence in Vojvodina is 5.14. Our study showed that the most unfavorable lung cancer incidence trends were present in age groups ranged from 45 to 49, 60 to 64, 65 to 69, and 70 to 74 years in men and in age groups ranged from 35 to 39, 40 to 44, and 45 to 49 years in women. We also found that the most unfavorable lung cancer mortality trends were present in age groups ranged from 45 to 49, 60 to 64, 65 to 69, and 70 to 74 years in men and in age groups range from 45 to 49 and 70 to 74 years in women. Favorable lung cancer mortality and incidence trend was present only in the age group ranged from 80 to 84 years in men. The highest percentage of diseased and deaths was in the age group ranged from 60 to 69 years for both sexes. In younger age groups the percentage of diseased was less than 2%. CONCLUSION: Preventive measures against lung cancer in our population do not show good results yet. This is either because of greater exposure of population to the risk factors or because of greater exposure to the risk factors of certain age cohorts. Decrease in sex ratio has shown that females are closing onto males when we talk about numbers of new lung cancer cases. It is clear that lung cancer incidence trends in males by age groups has shown greater variability while in females variability occurs on smaller scale when lung cancer incidence trends by age groups are discussed.